Pengaruh antioksidan ekstrak daun gambir (Uncaria gambir Roxb.) terhadap peningkatan aktivitas enzim katalase pada model tikus dengan stres oksidatif - Diah Septiyanti Kesumaningrum; Arum Setiawan; Zen Hafy (Holistik Jurnal Kesehatan, 2026)
Background: Oxidative stress contributes to the pathogenesis of degenerative diseases by decreasing the activity of endogenous antioxidant enzymes, including catalase. Gambier leaves (Uncaria gambir Roxb.) from Babat Toman, South Sumatra, contain bioactive compounds with potential antioxidant activity. Purpose: To analyze the bioactive compounds of gambier leaf extract from Babat Toman and evaluate their effect on catalase enzyme activity in Wistar rats experiencing oxidative stress induced by the Forced Swimming Test, and to determine the most effective dose. Method: This experimental study used a post-test-only randomized control group design with 25 male Wistar rats divided into five groups: negative control (K1), Forced Swimming Test control (K2), and treatment groups given gambier extract at doses of 50 mg/kgBW (K3), 75 mg/kgBW (K4), and 100 mg/kgBW (K5). The extract was obtained from Babat Toman gambir leaves through a maceration method using 96% ethanol. Bioactive compounds were analyzed using GC-MS, while catalase activity was analyzed using the Kruskal-Wallis and Mann-Whitney tests. Results: GC-MS showed that gambir extract was dominated by n-hexadecanoic acid (27.24%), hexadecanoic acid ethyl ester (24.80%), and heptadecanoic acid ethyl ester (12.03%). Catalase activity showed a significant difference between groups (χ² = 10.453; p = 0.033), with the Mann-Whitney test indicating that catalase activity in group K5 was significantly higher than in group K2 (p = 0.028) and approached the level of group K1. Conclusion: Gambir leaf extract from Babat Toman effectively increased catalase enzyme activity in rats experiencing oxidative stress due to the Forced Swimming Test, with 100 mg/kgBW being the most effective dose.   Keywords: Antioxidant; Catalase Enzyme; Gambir Leaf Extract (Uncaria gambir Roxb.); Oxidative Stress; Rats.